Inflammatory Papillitis in Uveitis: Response to Treatment and Use of Optic Nerve Optical Coherence Tomography for Monitoring. (3rd March 2016) - Cho, Heeyoon; Pillai, Parvathy; Nicholson, Laura; Sobrin, Lucia
Abstract: Purpose : To describe the clinical course of uveitis-associated inflammatory papillitis and evaluate the utility and reproducibility of optic nerve spectral domain optical coherence tomography (SD-OCT). Methods : Data on 22 eyes of 14 patients with uveitis-related papillitis and optic nerve imaging were reviewed. SD-OCT measure reproducibility was determined and parameters were compared in active vs. inactive uveitis. Results : Papillitis resolution lagged behind uveitis resolution in three patients. For SD-OCT measures, the intraclass correlation coefficients were 99.1–100% and 86.9–100% for intraobserver and interobserver reproducibility, respectively. All SD-OCT optic nerve measures except inferior and nasal peripapillary retinal thicknesses were significantly higher in active vs. inactive uveitis after correction for multiple hypotheses testing. Mean optic nerve central thickness decreased from 545.1 to 362.9 µm ( p = 0.01). Conclusions : Resolution of inflammatory papillitis can lag behind resolution of uveitis. SD-OCT assessment of papillitis is reproducible and correlates with presence vs. resolution of uveitis.